The red badge of courage - Crane, Stephen, 1871-1900 ([Boston, Mass] : Thomson Heinle, 2005)
In the spring of 1863, while engaged in the fierce Civil War battle of Chancellorsville in Virginia, a young Union soldier matures to manhood and finds peace of mind as he comes to grips with his conflicting emotions about war
Title from container
Keywords: Chancellorsville, Battle of, Chancellorsville, Va., 1863 -- Fiction; Historical fiction; War stories; United States x History -- Civil War, 1861-1865 -- Fiction